The High/Low Divide: Self- Selection by Values in Auction Choice - Radosveta Ivanova-Stenzel; Timothy C. Salmon (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Most prior theoretical and experimental work involving auction choice has assumed bidders only find out their value after making a choice of which autcion to enter. In this paper we examine whether or not subjects knowing their value prior to making an auction choice impacts their choice decision and/or the outcome of the auctions. The results show a strong impact. Subjects with low values choose the first price sealed bid auction more often while subjects with high values choose the ascending auction more often. The average numbers of bidders in both formats ended up being on average the same, but due to the self-selection bias the ascending auction raised as much revenue on average as the first sealed bid auction. The two formats also generate efficiency levels that are roughly equivalent though the earnings of bidders are higher in the ascending auction.
urn:nbn:de:bvb:19-epub-13259-1
Keywords: C91; D44; 330; bidder preferences; private values; sealed bid auctions; ascending auctions; endogenous entry; Auktionstheorie; Auswahl; Bewertung; Theorie